Basic Economics Knowledge of Prospective Economic Teachers in Surabaya: Based on Their Background - Prakoso, Albrian Fiky; Andriansyah, Eka Hendi; Solichin, M. Riadhos (Jurnal Pendidikan Ekonomi Undiksha, 2020)
Surabaya is the second-largest city in Indonesia. There is great hope for prospective teachers in Surabaya to have high credibility because their salaries are equivalent to the City Minimum Wage. The salary is the largest when compared to other cities in East Java province. The favorite field of science in social science is economics. However, to determine the basic economic knowledge that students will have in schools properly, it is the economics teacher who plays a big role. So it is necessary to research economic knowledge for prospective economics teachers before they become actual teachers. This study aims to determine how deep the basic knowledge of economics is in students of the Economic Education study program in Surabaya, where they are prospective economics teachers. This research method applies descriptive statistical methods. The survey was conducted on 338 students who are prospective economics teachers. There are only two Economic Education study programs in Surabaya, namely the State University of Surabaya (Unesa) and the IKIP Widya Darma Surabaya (IWIDA). All populations in this study were used as samples. The results showed that Unesa was indeed superior in understanding basic economics. The most important implication is that Unesa needs to pay special attention to prospective economic teachers who are female, come from private schools, come from outside the city of Surabaya, and come from SMK. Meanwhile, IWIDA needs to pay special attention to prospective economic teachers who are female, come from private schools, come from Surabaya, and come from MA.